Berteologi dengan Artifical Intelegence (AI) di Era Revolusi 5.0: Pemanfaatan Artificial Inteligence (AI) dalam Perkembangan Gereja untuk Mewujudkan Kesalehan Sosial di Era Revolusi 5.0 - Marulitua, Hasiholan (Universitas Methodist Indonesia, 2025)
In the current century, there is a lot of excitement about the use of artificial intelligence (AI) in human life. This includes the worlds of education, business, health and banking. The presence of AI makes it easier for everyone to carry out all their activities. AI replaces the role of humans in life. Will the AI ​​that humans have created make people more dependent on it, or will humans entrust their lives more to AI? This question will always arise from many circles. Next, how the Bible responds to this phenomenon is what we will see in this article.